The effect of loss of foot sole sensitivity on H-reflex of triceps surae muscles and functional gait - Zhang, Fangtong; Sun, Mengzi; Qu, Feng; Lewis, Kelsey; Choi, Jung Hun; Song, Qipeng; Li, Li (Frontiers in Physiology, 2023)
Objective: To investigate the effects of foot sole insensitivity on the outcomes of the triceps surae muscle H-reflex and functional gait. Material and Methods: People with peripheral neuropathy were recruited and divided into two groups: people with more (n = 13, 73.3 ± 4.3 years old) or less (n = 10, 73.5 ± 5.3) sensitive tactile sensation. Their monofilament testing scores were 9.0 ± 1.5 (range: 7–10) and 2.3 ± 2.4 (range: 0–6) out of 10, respectively. H-reflex of the triceps surae muscles during quiet standing and their relationship with functional gait, 6 min walking distance (6MWD), and timed-up-and-go duration (TUG), were compared between groups. Results: No significant difference was detected for H-reflex parameters between the groups. The less sensitive group showed reduced (p < .05) functional gait capacity compared to the other group, 38.4 ± 52.7 vs. 463.5 ± 47.6 m for 6MWD, and 9.0 ± 1.5 vs. 7.2 ± 1.1s for TUG, respectively. A significant correlation (p < .05), worse functional gait related to greater H/M ratio, was observed in the less sensitive group, not the other group. Conclusion: Although there was no significant H-reflex difference between the groups, more pronounced tactile sensation degeneration affected functional gaits and their relationship with H-reflex.